Analysis of Project Implementation Costs Using the Crashing Method in the Construction Work of Sunan Ampel Jombang Junior High School - Venusia A, M. Fajar; Wulandari, Esti; Witjaksana, Budi (Enrichment: Journal of Multidisciplinary Research and Development, 2025)
The development of educational infrastructure is a crucial aspect in supporting the improvement of the quality of learning and human resource development in Indonesia. However, in its implementation, construction projects often face challenges in the form of delays in completion and cost inefficiencies, which impact the disruption of the educational process and increase the budget. This study aims to analyze the cost efficiency and acceleration of the implementation time of the Sunan Ampel Jombang Junior High School construction project through the crashing method approach, which is a technique in project management used to accelerate project completion time by selectively adding resources to critical activities. The delay in the start of a project is the main problem faced by the implementers of the Sunan Ampel Jombang Junior High School construction project, resulting in delays in final completion and an inflated project value. Based on the analysis conducted, this study also provides solutions to overcome this. The results of the analysis of the Sunan Ampel Jombang Junior High School construction project show an additional cost of Rp. 163,845,745.00 from the normal work cost to Rp. 2,623,114,845.00, an increase of 0.93%. This research provides practical contributions for project managers and contractors in making strategic decisions related to controlling project time and costs and can be a reference in managing the risk of project delays in the future.